Communicating saccular pyloroduodenal duplication - Sjekavica, Ivica (Radiology and oncology (Ljubljana), 2005)
Background. Duplication anomalies of pyloroduodenal region are not common. Intestinal duplications should be considered if additional specific development malformations are present. Case report. We report a case of the pyloroduodenal duplication in 22-month-old girl by whom intermittent nausea and vomiting were the first symptoms. US revealed an anechoic cystic lesion between the stomach and the left liver lobe. The upper gastrointestinal contrast study revealed stenosis in the pylorobulbar region, as a result of the extrinsic compression. The diagnosis of the alimentary tract duplication cyst compressing the atypically formed head of pancreas was highly suspected by the contrast enhanced multi slice computerized tomography (MSCT). The intraoperative contrast application detected a communication between both, duplication and pyloric region. The patohistological examination confirmed a duplication cyst containinggastric and duodenal mucosa with no ectopic pancreatic tissue. Conclusions. The ultrasound examination, as the initial diagnostic procedure of intestinal duplication, usually reveals a cystic anechoic lesion. Additional barium study, contrast enhanced CT or MRI scan areuseful in diagnosis of alimentary tract duplications, providing supplementary information.
Keywords: Abnormalities; anomalije; baby; Contrast Media; črevesje; diagnostika; Dojenček; Duodenum; Dvanajstnik; Infant; Kontrastna sredstva; Pilorus; Pylorus; Radiography; ultrazvočna diagnostika